2008
DOI: 10.1126/science.1162219
|View full text |Cite
|
Sign up to set email alerts
|

Ages for the Middle Stone Age of Southern Africa: Implications for Human Behavior and Dispersal

Abstract: The expansion of modern human populations in Africa 80,000 to 60,000 years ago and their initial exodus out of Africa have been tentatively linked to two phases of technological and behavioral innovation within the Middle Stone Age of southern Africa—the Still Bay and Howieson's Poort industries—that are associated with early evidence for symbols and personal ornaments. Establishing the correct sequence of events, however, has been hampered by inadequate chronologies. We report ages for nine sites from varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
349
3
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(368 citation statements)
references
References 28 publications
10
349
3
4
Order By: Relevance
“…The relative numbers of rejected grains are similar to those of other OSL studies, e.g. in Jacobs et al (2008a) the corresponding numbers are (i) 24 ± 1 % and (ii) 1.8 ± 0.2 % (n = 48 samples). However, we observe no significant changes in the dose recovery ratio or in the dispersion in the equivalent dose distribution (i.e.…”
Section: Dose Recovery Experimentssupporting
confidence: 72%
“…The relative numbers of rejected grains are similar to those of other OSL studies, e.g. in Jacobs et al (2008a) the corresponding numbers are (i) 24 ± 1 % and (ii) 1.8 ± 0.2 % (n = 48 samples). However, we observe no significant changes in the dose recovery ratio or in the dispersion in the equivalent dose distribution (i.e.…”
Section: Dose Recovery Experimentssupporting
confidence: 72%
“…In particular, it is often argued in the literature that typical OD values for wellbleached, single dose component samples are lower than 20 %. For example, Jacobs et al (2008) state that, based on the work by Olley et al (2004b) "samples consisting of well-bleached quartz grains commonly have De distributions that are overdispersed by up to 20%"; then, they "ran the FMM using σ d values of between 10 and 20%" (Jacobs et al, 2008;Supporting Online Material, p. 13). On the same subject of the application of the FMM to identify well-bleached components, and in particular when justifying that a maximum of 20 % for the OD value is used to run the FMM, Jacobs et al (2011) state that "there is little merit *…+ in using very high OD values (NB: greater than 20%), as the latter are poor analogues for a wellbleached sample" (see Supplementary Material, p. 17).…”
Section: Results: Compared Single-grain Agesmentioning
confidence: 99%
“…However, equivalent studies of OSL signals of single quartz grains (Jacobs et al, 2008) have indicated that single grain measurements provide a way to reject grains with aberrant behaviour, thus increasing the precision of ages. A similar approach, i.e.…”
Section: E Determination Using Single Kf Grainsmentioning
confidence: 99%